Prenatal and early life exposure to stressful life events and risk of autism spectrum disorders: population-based studies in Sweden and England. - Dheeraj Rai; Jean Golding; Cecilia Magnusson; Colin Steer; Glyn Lewis; Christina Dalman (PLoS ONE)
Background and aim Exposure to stressful life events during pregnancy has been suggested as a potential risk factor for offspring Autism Spectrum Disorders (ASD), but the literature is limited and inconsistent. We tested the hypothesis that maternal exposure to stressful life events would be associated with increased risks of offspring ASD, and that these risks would be highest for exposures during the prenatal period. Methods and results We used prospectively collected data from two large population based studies in Sweden and England. In the Swedish study of 4429 ASD cases and 43277 controls, our exposure comprised the occurrence of any severe life event before and during pregnancy and the child's early life. In the English study (maximum n = 11554, ASD n = 72), we studied the risk of offspring ASD in relation to a combined maternal exposure to multiple (up to 42) common and rare life events, as well as their perceived impact upon the mother during pregnancy and early life. In crude and adjusted regression analyses in both studies, we found no evidence of an association between prenatal life events, or their number and perceived impact and the risk of offspring ASD. Sub-group analysis of ASD with and without intellectual disability in the Swedish study yielded similar results. Conclusion We found no evidence to support the hypotheses that exposure to stressful life events during the prenatal period is associated with an increased risk of offspring ASD.